2006
DOI: 10.1080/00071660600611169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endothelial and inducible nitric oxide synthase mRNA expression in the lung of broiler chickens with developmental pulmonary hypertension due to cold stress

Abstract: To clarify the effect of cold-induced pulmonary hypertension on endothelial and inducible nitric oxide synthase (eNOS and iNOS) mRNA expression in the lung of broiler chickens, semi quantitative reverse transcription-PCR was performed on total RNAs isolated from lungs of the broiler chickens exposed to 5 weeks of cold stress. The eNOS gene was expressed increasingly with the increasing age during the rearing period. Comparing the treatment group with its related control group eNOS was expressed significantly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…When eNOS and iNOS are inhibited, the ensuing reduction in NO synthesis leads to pulmonary arterial vasoconstriction, pulmonary hypertension, and PAH (Wideman et al, , 1996a(Wideman et al, , 1998b(Wideman et al, , 2005a(Wideman et al, ,b, 2006Grabarevic et al, 1997;Martinez-Lemus et al, 1999Villamor et al, 2002;Weidong et al, 2002;Hernandez, 2003, 2006;Odom et al, 2004;Bowen et al, 2006a,b;Ruiz-Feria, 2009). Reduced pulmonary arteriolar eNOS expression was reported in broilers developing PAH during chronic exposure to hypobaric hypoxia (Moreno de Sandino and Hernandez, 2003Hernandez, , 2006, but pulmonary eNOS and iNOS expression levels were not correlated with the onset of PAH induced by chronic exposure to sub-thermoneutral temperatures (Teshfam et al, 2006). Cardiac gene expression for iNOS was impaired in broilers with pulmonary hypertension compared with control broilers (Hassanpour et al, 2009).…”
Section: Mediators Of Pulmonary Vasodilationmentioning
confidence: 92%
“…When eNOS and iNOS are inhibited, the ensuing reduction in NO synthesis leads to pulmonary arterial vasoconstriction, pulmonary hypertension, and PAH (Wideman et al, , 1996a(Wideman et al, , 1998b(Wideman et al, , 2005a(Wideman et al, ,b, 2006Grabarevic et al, 1997;Martinez-Lemus et al, 1999Villamor et al, 2002;Weidong et al, 2002;Hernandez, 2003, 2006;Odom et al, 2004;Bowen et al, 2006a,b;Ruiz-Feria, 2009). Reduced pulmonary arteriolar eNOS expression was reported in broilers developing PAH during chronic exposure to hypobaric hypoxia (Moreno de Sandino and Hernandez, 2003Hernandez, , 2006, but pulmonary eNOS and iNOS expression levels were not correlated with the onset of PAH induced by chronic exposure to sub-thermoneutral temperatures (Teshfam et al, 2006). Cardiac gene expression for iNOS was impaired in broilers with pulmonary hypertension compared with control broilers (Hassanpour et al, 2009).…”
Section: Mediators Of Pulmonary Vasodilationmentioning
confidence: 92%
“…Acute cold stress groups (1, 3, 6, 12, and 24 h), 0 h=acute cold stress control group, chronic cold stress groups (5s, 10s, and 20s), and chronic corresponding control groups (5c, 10c, and 20c) means of establishing a host defense, increases in iNOS and COX-2 expression have been implicated in various pathophysiological processes of septic shock and chronic inflammatory diseases, with iNOS proposed to play a proinflammatory role. Prior research (Teshfam et al 2006) indicated that cold exposure could significantly increase eNOS and iNOS gene expression in the lungs of broiler chickens. Acute immobilization and cold water-immersion stress increased TNF-α level at different time points (0, 30, 60, and 120 min) after stress in rats (Liu et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Broilers are more sensitive to heart failure in comparison with other strains of chickens. Factors such as body performance, oxygen demands, hematological parameters, and cellular interactions may all be involved in the resistance or susceptibility of broilers to heart failure and pulmonary hypertension syndrome (PHS) (2). This syndrome is the most important cardiomyopathy in industrial broilers (3,4).…”
Section: Introductionmentioning
confidence: 99%